Study on changes in tourism land and influence factors in mountain areas: A case study of Luanchuan country, China - Yanna Xie; Qingxiao Zhu; Genghe Gao; Lisheng Zhang (Global Journal of Ecology - Peertechz Publications, 2021)
The rapid development of the tourism industry in mountainous areas has resulted in intense changes in land use structure and has exerted a strong influence on terrestrial ecosystems. This paper takes Luanchuan County (with typical mountainous terrain in western Henan Province, China) as an example and employs land use data from different times and areas and the binary logistic method to study the spatial variation in tourism land and influencing factors in mountainous areas. The research shows that (1) the spatial variation in land use in scenic spots reveals a chain reaction of land use type transformation caused by construction land expansion, a key driving force of spatial variation in land use and land use type transformation, and (2) the changes in tourism land use types result from human utilization and development of land for economic benefits. The key influencing factors of the spatial variation in land use are elevation, gradient, and the distances to rivers, highways and villages. (3) A plan for tourism land management and control should be established with construction land as the key indicator.